PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MICROSOFT OFFICE POWERPOINT PADA MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) KELAS VII SEMESTER GENAP DI SMP N 4 TABANAN KABUPATEN TABANAN TAHUN PELAJARAN 2012/2013 - ., I Gede Putu Adhiyasa Surya Pratama; ., Drs. Ketut Pudjawan,M.Pd; ., Drs. I Dewa Kade Tastra,M.Pd (Jurnal EDUTECH Undiksha, 2014)
Penelitian ini bertujuan: (1) Mengetahui prosedur pengembangan media pembelajaran dengan software Powerpoint pada mata pelajaran Teknologi Informasi dan Komunikasi (TIK) untuk kelas VII; (2) menghasilkan suatu produk media pembelajaran Powerpoint untuk mata pelajaran Teknologi Informasi dan Komunikasi (TIK) untuk kelas VII di SMP N 4 Tabanan dalam bentuk CD yang layak untuk diterapkan sebagai media pembelajaran. Penelitian ini menggunakan pendekatan penelitian pengembangan (Research and Development) yang dilakukan di SMP Negeri 4 Tabanan, Kabupaten Tabanan dalam waktu tujuh bulan, mulai dari bulan April 2013 sampai dengan bulan Oktober 2013. Objek penelitian ini berupa pengembangan media pembelajaran dengan Powerpoint pada mata pelajaran Teknik Informasi dan Komunikasi (TIK) dengan materi perangkat keras komputer. Metode pengembangan yang digunakan adalah metode prosedural yang diadaptasi dari model pengembangan desain instruksional menurut Dick & Carey dan model penelitian pengembangan menurut Borg & Gall. Instrumen pengumpulan data berupa lembar angket untuk ahli materi, ahli desain, dan ahli media, uji coba perorangan, kelompok kecil dan lapangan. Analisis data menggunakan analisis deskriptif kualitatif yaitu digunakan untuk mengolah data hasil review yang berupa masukan, tanggapan, kritik dan saran perbaikan yang terdapat pada kuesioner, dan analisis data deskriptif kuantitatif yaitu digunakan untuk mengolah data berupa angka-angka atau persentasi yang diperoleh melalui kuesioner dalam penilaian media pembelajaran yang dikembangkan. Hasil penelitian ini adalah media pembelajaran dengan Powerpoint yang dikemas dalam sebuah CD (compact disc), sedangkan prosedur pengembangan media pembelajaran yang dilakukan yaitu: (1) analisis yang meliputi analisis spesifikasi teknis dan tahap analisis kerja program; (2) membuat storyboard; (3) desain program yang meliputi desain diagram alir, dan desain interface; (4) implementasi program; dan (5) pengujian. Media pembelajaran dinyatakan layak berdasarkan uji kelayakan menurut: (1) uji ahli isi mata pelajaran TIK berada pada kualifikasi sangat baik (93,33%), (2) uji ahli desain pembelajaran berada pada kualifikasi baik (84%), (3) uji ahli media pembelajaran berada pada kualifikasi baik (86,67%), (4) uji coba perorangan berada pada kualifikasi baik (82.96%), uji kelompok kecil berada pada kualifikasi sangat baik (92,51%), uji coba lapangan berada pada kualifikasi baik (89%). Dari hasil uji di atas dapat disimpulkan bahwa media pembelajaran dengan Powerpoint yang dikembangkan layak digunakan sebagai pendukung pembelajaran untuk mata pelajaran TIK pada kelas VII.Kata Kunci : pengembangan, powerpoint, mata pelajaran TIK This study aims to : ( 1 ) designing and creating instructional media with Powerpoint software on the subjects of Information and Communication Technology ( ICT ) for class VII , (2 ) produce a software product for subjects learning Powerpoint Information and Communication Technology ( ICT ) for the class VII in SMP N 4 Tabanan in CD eligible to apply as a medium of learning. This study aims to: (1) Determine the instructional media development procedures with Powerpoint software on the subjects of Information and Communication Technology (ICT) for class VII, (2) produce a media product for subjects learning Powerpoint Information and Communication Technology (ICT) for class VII in SMP N 4 Tabanan in CD which worth to apply as a learning media. This research approach development research ( Research and Development ) conducted in SMP Negeri 4 Tabanan Tabanan within seven months , starting from April 2013 to October 2013 . Object of this research is the development of instructional media on subjects with Powerpoint Engineering Information and Communication ( ICT ) with the material of computer hardware . The method used is the development of procedural methods adapted from the model of the development of instructional design by Dick & Carey model of research and development by Borg & Gall . Data collection instruments in the form of a questionnaire sheet to matter experts , design experts , and media experts , individual testing , small groups and field . Analysis of data using qualitative descriptive analysis that is used to process the results of a review of data in the form of input , feedback , critiques and suggestions for improvements contained in the questionnaires , and analysis of quantitative descriptive data that is used to process the data in the form of numbers or percentages obtained through questionnaires in the assessment instructional media developed . The results of this research is to study media Powerpoint packaged in a CD ( compact disc ) , while the instructional media development procedures performed are: ( 1 ) analysis includes analysis of technical specification and analysis phase work program , (2 ) create a storyboard ; ( 3 ) design programs that include design flow charts , and interface design , (4 ) implementation , and ( 5 ) testing . Learning media declared eligible by the feasibility test by: ( 1 ) test expert ICT course content was very good in qualifying ( 93.33 % ) , ( 2 ) test instructional design experts are in good qualifications ( 84 % ) , ( 3 ) test instructional media specialists are in good qualifying ( 86.67 % ) , ( 4 ) the trial was well-qualified individuals ( 82.96 % ) , a small group of test are in excellent qualifications ( 92.51 % ) , field trials are in qualifying good ( 89 % ) . From the test results it can be concluded that the instructional media developed with Powerpoint decent used as learning support for ICT subjects in class VII. Results of this study was to Powerpoint learning media is packaged in a CD ( compact disc ) , while the procedure is performed to produce instructional media , namely : ( 1 ) the analysis includes the analysis of the technical specification and analysis phase of the work program , (2 ) create a storyboard ; ( 3 ) program which includes the design flow chart design , and interface design , (4 ) implementation , and ( 5 ) testing . Instructional media declared eligible by the feasibility test by: ( 1 ) test expert ICT course content is in a very good qualifying ( 93.33 % ) , ( 2 ) test instructional design experts are on good qualifications ( 84 % ) , ( 3 ) test learning media is expert in both qualifying ( 86.67 % ) , ( 4 ) individual testing on both qualifying ( 82.96 % ) , small group test is in excellent qualifications ( 92.51 % ) , field trials are on qualifications good ( 89 % ) . From the test results it can be concluded that the instructional media developed with Powerpoint decent used as learning support for ICT subjects in class VII . keyword : development, powerpoint, ICT